School phobia - Alina Gabriela Anghel (Association of Social and Educational Innovation, 2016)
School phobia is identified as a problem met frequently in today's society, where the specialists in educational and social policies are actively preoccupied to identify efficient intervention strategies to prevent and fight it. The reasons are extremely diverse: internal - having to do with the alteration of the emotional background due to stressors affecting one emotionally significantly, and external - having to do with the school environment. The multisectorial and pluridisciplinary intervention for each case in turn and the functioning of the school-family partnerships can contribute successfully to the prevention of and fight against the cases of school phobia. At the same time, the correct implementation with the child of education models achievable in relation to his intellectual potential decreases the risk of emergence of school phobia. The active school-family partnerships successfully empower the intervention strategies in solving different situations of educational crisis that favor the settling in of school phobia. This research aims to analyze the parents' perception concerning the way one can intervene in cases of children identified with school phobia. The research has been realized on a lot of parents in the rural area. The research results have led to the following conclusion: the specialists in the school framework are those who must act during a first stage in the prevention and fight against the cases of school phobia.